Effects Of Different Doses Of Probiotic (Biomin)® On Some Hematological And Biochemical Parameters In Chicken - N. Mustafa (College of Education for Pure Sciences, 2009)
ABSTRACT This study was carried out to evaluate effects of probiotic (BIOMIN)® at different doses (0.15, 0.3, 1.5, 7.5, 15 g/kg diet) on some hematological and biochemical parameters in chickens. The number of broiler chickens are 48 at one day old Ross kind were used . Results show that body weight increased significantly (p≤0.05) as probiotic dose, while both Hb concentration and PCV% are not changed in relation to probiotic doses. Reduction of serum cholesterol level was clear and dependent on the contrary changes in both serum protein and urea, which inceased with dose elevation, on the other hand, serum glucose level changes unclearly in different dose groups. Finally results show very high dose (15 g/kg diet) of probiotic (BIOMIN)® lead to death of all chickens in this group at the 3rd day of experiment.